2016
DOI: 10.1002/ptr.5570
|View full text |Cite
|
Sign up to set email alerts
|

Grapes (Vitis vinifera) as a Potential Candidate for the Therapy of the Metabolic Syndrome

Abstract: Metabolic syndrome is associated with several disorders, including hypertension, diabetes, hyperlipidemia as well as cardiovascular diseases and stroke. Plant-derived polyphenols, compounds found in numerous plant species, play an important role as potential treatments for components of metabolic syndrome. Studies have provided evidence for protective effects of various polyphenol-rich foods against metabolic syndrome. Fruits, vegetables, cereals, nuts, and berries are rich in polyphenolic compounds. Grapes (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(80 citation statements)
references
References 135 publications
(187 reference statements)
0
78
0
2
Order By: Relevance
“…There are many in vivo studies reporting the antidiabetic activity of grape and grape byproduct polyphenols, especially grape seed extracts. Studies have shown that different proteins and enzymes are involved in these antidiabetic activities (Akaberi and Hosseinzadeh, ). V .…”
Section: Pharmacological Effectsmentioning
confidence: 97%
“…There are many in vivo studies reporting the antidiabetic activity of grape and grape byproduct polyphenols, especially grape seed extracts. Studies have shown that different proteins and enzymes are involved in these antidiabetic activities (Akaberi and Hosseinzadeh, ). V .…”
Section: Pharmacological Effectsmentioning
confidence: 97%
“…Guilford et al (96) indicated that regular red wine consumption is associated with a 30% risk reduction for type 2 diabetes. Consumption of grape seed polyphenols and red wine grape pomace flour have been associated with significant reductions in blood glucose (37,97). Conversely another study found no effect of grape juice polyphenols in healthy individuals (38).…”
Section: Polyphenolsmentioning
confidence: 99%
“…Studies have provided evidence for protective effects of various polyphenol-rich foods against metabolic syndrome. Standard food enrichments such as fruits, vegetables, cereals, nuts, and berries are rich in polyphenolic compounds [2]. Grapes (Vitis vinifera), especially grape seeds, stand out as rich sources of antioxidants and have been reported to inhibit the risk factors involved in metabolic syndrome such as hyperlipidemia, hyperglycemia, and hypertension in both humans and animals.…”
Section: Where Is the Cyclone?mentioning
confidence: 99%